Distant metastasis risk and prognosis in elderly gastric cancer patients after neoadjuvant chemotherapy and surgery - Shang, Jiarong; Zhu, Jin; Zheng, Xia; Shao, Yujia; Qian, Jun; Li, Yong; Wang, Ping (Frontiers in Oncology, 2026)
BackgroundGastric cancer imposes a heavy global health burden, and treatment evaluation in elderly patients is often more complex. Although NAC is standard for locally advanced gastric cancer (LAGC), benefits in the elderly are heterogeneous, postoperative distant metastasis (DM) is underexplored, and no nomogram specifically evaluates postoperative DM diagnosis and prognosis in elderly LAGC after NAC.MethodsThis study extracted data from patients over 70 years of age who were diagnosed with gastric adenocarcinoma and underwent neoadjuvant chemotherapy followed by curative gastrectomy between 2016 and 2022. Independent risk factors for postoperative distant metastasis following neoadjuvant chemotherapy were identified using univariate and multivariate logistic regression analyses, while independent prognostic factors were determined through univariate and multivariate Cox proportional hazards regression analyses. Subsequently, we developed two novel nomograms and evaluated their performance using receiver operating characteristic (ROC) curves, calibration curves, and decision curve analysis (DCA).ResultsA total of 896 elderly gastric adenocarcinoma patients were enrolled, among whom 307 (34.26%) developed postoperative DM. Independent risk factors for DM included N stage, NAC-related adverse events, CA19–9 levels, NLR, tumor nodules, resection margin status, tumor regression grade, as well as intraoperative and postoperative chemotherapy. Among DM patients, independent prognostic predictors included CA72–4 levels, NLR, NAC-to-surgery interval, tumor regression grade, resection margin status, and postoperative chemotherapy. Both nomograms demonstrated high predictive accuracy, supported by ROC analysis, calibration curves, decision curve analysis, and Kaplan-Meier survival analysis in the training and validation sets.ConclusionsThe two nomograms show promise as effective tools for predicting the risk of postoperative distant metastasis and estimating personalized prognosis in elderly gastric cancer patients following neoadjuvant chemotherapy, thereby potentially informing clinical decision-making.